Role of Vitamin K in Intestinal Health - Lai, Yujiao; Masatoshi, Hori; Ma, Yanbo; Guo, Yuming; Zhang, Bingkun (Frontiers in Immunology, 2022)
Intestinal diseases, such as inflammatory bowel diseases (IBDs) and colorectal cancer (CRC) generally characterized by clinical symptoms, including malabsorption, intestinal dysfunction, injury, and microbiome imbalance, as well as certain secondary intestinal diseases complications, continue to be serious public health problems worldwide. The role of vitamin K (VK) on intestinal health has drawn growing interest recent years. In addition to its role in blood coagulation and bone health, several investigations continue to explore the role of VK as an emerging novel biological compound with the potential function of improving intestinal health. This study aims to present a thorough review on the bacterial sources, intestinal absorption, uptake of VK, and VK deficiency in patients with intestinal diseases, with emphasis on the effect of VK supplementation on immunity, anti-inflammation, intestinal microbes and its metabolites, anti-oxidation and coagulation, and promoting epithelial development. Besides, VK-dependent proteins (VKDPs) is another crucial mechanism for VK to exert gastroprotection role for their functions of anti-inflammation, immunomodulation and anti-tumorigenesis. In summary, published studies preliminarily show that VK presents a beneficial effect on intestinal health and may be used as a therapeutic drug to prevent/treat intestinal diseases, but the specific mechanism of VK in intestinal health has yet to be elucidated.